Microcatheter shaping using three-dimensional printed models for intracranial aneurysm coiling. (28th September 2019) - Xu, Y; Tian, W; Wei, Z; Li, Y; Gao, X; Li, W; Dong, B
Abstract : Background and purpose: Microcatheterization is an important, but also difficult, technique used for the embolization of intracranial aneurysms. The purpose of this study was to investigate the application of three-dimensional (3D) printing technology in microcatheter shaping. Methods: Nine cases of internal carotid artery posterior communicating artery aneurysm diagnosed by CT angiography were selected, and 3D printing technology was used to build a 3D model including the aneurysm and the parent artery. The hollow and translucent model had certain flexibility; it was immersed in water and the microcatheter was introduced into the water to the target position in the aneurysm, followed by heating the water temperature to 50°C. After soaking for 5 min, the microcatheter was taken out and the shaping was completed. After sterilization, the shaped microcatheter was used for arterial aneurysm embolization and evaluation was conducted. Results: Nine cases of microcatheter shaping were satisfactory and shaping the needle was not necessary; no rebound was observed. The microcatheter was placed in an ideal position, and the stent-assisted method was used in three cases of wide-neck aneurysm. There were no complications related to surgery. Conclusion: A new microcatheter shaping method using 3D printing technology makes intracranial artery aneurysm embolization more stable and efficient.